2019
DOI: 10.18689/mjaes-1000110
|View full text |Cite
|
Sign up to set email alerts
|

Land Tenure Systems and Agricultural Productivity in Gombe Nigeria

Abstract: The purpose of this study is to examine the existing land tenure systems in Gombe state Nigeria with a view to determining its impact on agricultural productivity in the study area. The targeted population for the study comprised of 7,832 households in purposively selected agrarian settlements cutting across the 3 senatorial districts in Gombe state Nigeria. The population was stratified into three zones and two locations were selected from each zone. The sample size for the study comprised of 500 households i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 6 publications
(15 reference statements)
5
12
0
Order By: Relevance
“…From the participants' responses, which was further depicted on the semantic networks in Figure 2, it was revealed that firstly, the dominant land tenure systems practised in the study area were mainly the customary and informal tenure systems. This finding is congruent with similar African based studies such as Lawal et al (2019) and Dabara et al (2019). Secondly, the participants identified three means by which they acquired their land, which include purchase, leasing and squatting.…”
Section: Level Of Lts Among Female-led Households Of Tulasupporting
confidence: 89%
See 3 more Smart Citations
“…From the participants' responses, which was further depicted on the semantic networks in Figure 2, it was revealed that firstly, the dominant land tenure systems practised in the study area were mainly the customary and informal tenure systems. This finding is congruent with similar African based studies such as Lawal et al (2019) and Dabara et al (2019). Secondly, the participants identified three means by which they acquired their land, which include purchase, leasing and squatting.…”
Section: Level Of Lts Among Female-led Households Of Tulasupporting
confidence: 89%
“…This is necessary because it has been found that women are more involved in food production at household levels; and that there is a nexus between LTS and FS (Dokken, 2015). Similarly, in Nigeria, LTS was found to significantly impact on production in the Agricultural sector (Dabara et al, 2019). Other factors impacting on FS as observed by scholars include the size of a household, the size of family's cultivable land, and the income level of the household's head (Abu & Soom, 2016).…”
Section: Literature Review/theoretical Frameworkmentioning
confidence: 90%
See 2 more Smart Citations
“…The state governors provide the right of occupancy for land users. However, majority of the land in Nigeria, especially agricultural lands, are still unregistered with a proof of right of occupancy [47,48]. Consequently, majority of the farmers still suffer from tenure insecurity.…”
Section: Discussionmentioning
confidence: 99%